If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(1x+2)=1 (2+3x)
We simplify the equation to the form, which is simple to understand
2(1x+2)=1(2+3x)
Reorder the terms in parentheses
+(+2x+4)=1*(2+3x)
Remove unnecessary parentheses
+2x+4=+1+*(+2+3x+)
Reorder the terms in parentheses
+2x+4=+(+2+3x)
Remove unnecessary parentheses
+2x+4=+2+3x
We move all terms containing x to the left and all other terms to the right.
+2x-3x=+2-4
We simplify left and right side of the equation.
-1x=-2
We divide both sides of the equation by -1 to get x.
x=2
| 3x-4x+1=-2x+5+5x | | x+2=-x-3 | | 5x+2+2x-7=7 | | 12x^2-92x-68=0 | | 3.7w=11.1 | | 7x+146= | | 18x+2=99-21-28x | | 8(1-y)-3(y+2)=2(y+1) | | 3x-6y+10=0 | | 7x-9-11-x=12 | | 8(1-x)-3(2-2x)=2(x+1) | | 5y+27+4y=9 | | 57-5x=4x+23 | | 4x(x-7)+13=27 | | 8-7x=31-4x | | 8.7=d+8.7 | | 5x-(2x+3)=4x-30 | | 4(7x+7)-5=28x+23 | | y=11x^2-90x-68 | | 15x+6y=0 | | (16+2x)*(16+2x)=228 | | 4x-8=4(x+4) | | 4(w+2x)+9w= | | 1.5=r+4.5 | | 1.5=r | | 2x-2y=11 | | 9(3x-5)=(5x+3)+7 | | 5x+1=8x+6 | | -18=162 | | -4(3a+2)=52 | | 48400=(2x+2)(x) | | y=25x^2+10x-24 |